Project cost and time key factors distressing building construction projects of Sindh Pakistan: a post-pandemic approach - Haseeb Haleem Shaikh; Noor Yasmin Zainun; Shabir Hussain Khahro (Archives of Civil Engineering, 2023)
The construction industry plays a major role in the boost of the country’s economy, providing basic facilities for residential and creating thousands of job opportunities. During COVID-19, the construction sectors in Sindh Pakistan was highly suffered and leading to delays in the completion of projects. As the construction sector was globally affected, building construction projects were also affected by completing the projects on estimated time and cost. Thus, this research investigates the significant factors of time and cost that affected the Hyderabad building construction projects during COVID-19 situation. Questionnaire surveys were designed to collect data from the employees working on building projects in Sindh Pakistan. The collected data was analyzed through the Average Index method. Unsafe working environment; shortage of workers; and increasing project cost was observed as significant factors that were highly affected during COVID-19. The results and findings shall be supportive for stakeholders to take into consideration of factors in the early stage of the expected pandemic situation. This research suggested that the stakeholders shall modify or amend the contract clause regarding for pandemic situation and incorporate the identified factors in the contract that should be considered by stakeholders to save the time and cost of the projects.